ANALISIS PELAKSANAAN BANTUAN SOSIAL PADA PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) DI KABUPATEN SIGI - Machfudz, Machfudz; Palampanga, Anhulaila M.; Kahar, Abdul (Katalogis, 2018)
The study focuses on analyzing the implementationof social assistance in the social assistance agency/board and its benefits to people with social welfare problems (PMKS) in Sigi District. Type of study is qualitative. Data collecting method includes interview, observations, and conclusion. The implementation of social assistance during 2015-2016 equals to Rp. 4. 474. 426. 700. Social assistance by Social Agency to handle 8 PMKS equals to Rp. 1. 624. 926. 700 or 36%. While the implementatin of social assistance is more in The Agency of Financial and Regional Asset, they only handle 3 PMKS worth Rp. 2.849.500.000 or 64%. There is a budget difference of Rp. 1.224.573.300. On the other hand, these institutions own different assignments in social welfare as stated in Law No. 11/2009 about social welfare. Of a total of Rp. 2.177.879.600 the amount of funds used for social assistance in Sigi in 2015-2016 only Rp. 1. 871. 379. 600 or 86% perceived benefits in the form of goods, while Rp. 300. 500. 000 or 14% in the form of money. Although the implementation of the social assistance in Sigi District is not as much as the funds in the Agency of Financial and Regional Asset, the social assistance budget ini Sigi is more beneficial for the PMKS.